The Neural Implementation of Surgical Expertise Within the Mirror-Neuron System: An fMRI Study - Kok, Ellen; De Bruin, Anique B.; Geel, Koos van; Gegenfurtner, Andreas; Heyligers, Ide; Sorger, Bettina (Frontiers in Human Neuroscience, 2018)
Motor expertise is an important aspect of high-level performance in professional tasks such as surgery. While recently it has been shown that brain activation as measured by functional magnetic resonance imaging (fMRI) within the mirror-neuron system (MNS) is modulated by expertise in sports and music, little is known about the neural underpinnings of professional, e.g., surgical expertise. Here, we investigated whether and (if so) how surgical expertise is implemented in the MNS in medical professionals across three levels of surgical qualification. In order to answer the more specific research question, namely, if the neural implementation of motor expertise develops in a linear or non-linear fashion, the study compares not only brain activation within the MNS related to action observation of novices and experts, but also intermediates. Ten novices (medical students), ten intermediates (residents in orthopedic surgery) and ten experts (orthopedic surgeons) watched 60 5 s video clips (5 s each) of daily-life activities and surgical procedures each while their brain activation was measured using a 3-T fMRI scanner. An established localization procedure was followed to functionally define the MNS for each participant individually. A 2 (video type: daily-life activities, surgical procedures) × 3 (expertise level: novice, intermediate, expert) ANOVA yielded a non-significant interaction. Furthermore, separate analyses of the precentral and parietal part of the MNS also yielded non-significant interactions. However, post-hoc comparisons showed that intermediates displayed marginally significantly lower brain activation in response to surgery-related videos within the MNS than novices. No other significant differences were found. We did not find evidence for the hypothesis that the brain-activation level in the MNS evoked by observing surgical videos reflects the level of surgical expertise in the professional task of (orthopedic) surgery. However, the results suggest a potential non-linear relationship between expertise level and MNS-activation level.